*This preview shows
pages
1–3. Sign up
to
view the full content.*

This
** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*
**Unformatted text preview: **Taylor Series, Taylor Polynomials John E. Gilbert, Heather Van Ligten, and Benni Goetz In the previous lecture we started with a power series like ∑ n a n x n or ∑ n a n ( x- c ) n and used it to define a function f ( x ) . Now we want to reverse the process by starting with a function f ( x ) and trying to represent it as a power series f ( x ) = ∑ n a n x n or f ( x ) = ∑ n a n ( x- c ) n centered at some point x = c . But what’s a n in this case? The answer is contained in one of the most fundamental results in single variable calculus: Definition: for a function f the Taylor Series of f centered at x = c is f ( x ) = f ( c ) + f ( c )( x- c ) + f ( c ) 2! ( x- c ) 2 + . . . + f ( n ) ( c ) n ! ( x- c ) n + . . . . When the Taylor series is centered at the origin it becomes f ( x ) = f (0) + f (0) x + f (0) 2! x 2 + . . . + f ( n ) (0) n ! x n + . . . = ∞ n =0 f ( n ) n ! x n , and it is then often called the Maclaurin Series of f . Technically speaking, there are functions f where the Taylor series does not converge to f ( x ) , but these rarely occur ‘in practice’, so we shall simply assume that when a Taylor series converges, it converges to f ( x ) and speak of the Taylor series representation of f ( x ) . Before trying to understand why the coefficients are the way they are, let’s look at some already familiar examples: Example 1: f ( x ) = 1 1- x Solution: since f ( x ) = 1 1- x = ⇒ f ( x ) = 1 (1...

View
Full
Document